Academic Writing Course. Editing, layout and proofreading with MS Word - Torres-Salinas, Daniel (Infonomy, 2024)
Second article in the series of four from the “Academic Writing Course”. This article reviews the essential functionalities of Microsoft Word. The main options are examined from the perspective of editing, formatting, and reviewing texts. The first section highlights the advanced options of Word, and then details layout options such as configuration, page orientation, line spacing, and line numbers. Next, the References menu is examined, focusing on the creation of indexes and tables of contents among other features. In the review section, comments, spell check, track changes, and split screen are highlighted. In short, this article provides a quick guide to the aspects of Word that we must master if we want to write fluently and present professional documents.